(untitled) (GAIMS Journal of Medical Sciences, 2023)
Introduction: Understanding the renal vascular anatomy is essential for a safe and effective donor nephrectomy, which ultimately affects the function and longevity of the renal graft in recipients of kidney transplants. The aim of this study was to study the incidence of accessory renal arteries in 100 potential renal donors. Materials and Methods: Over a period of 24 months, a prospective assessment of consecutive intra-arterial digital angiograms of 100 potential kidney donors was conducted. Anatomical variations of renal arteries, such as auxiliary arteries, were noted. Results: Out of the 100 donors, 22% were found to have accessory renal arteries. Conclusions: Donors with accessory renal vessels are avoided for renal transplant surgeries because of the post operative complications.